2003
DOI: 10.1161/01.cir.0000080292.11186.fb
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Thallium Scanning, Selective Coronary Revascularization, and Long-Term Survival After Major Vascular Surgery

Abstract: Background-Ischemia on thallium scanning is a strong predictor of long-term mortality in CAD patients. Whether coronary revascularization (CR) in patients with significant ischemia on preoperative thallium scanning (PTS) improves long-term survival after major vascular surgery has not been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…28 However, thallium scanning may not be fully reliable as a predictor of asymptomatic significant coronary artery disease, especially in patients with left main or three vessel disease who are most at risk of post-operative and longterm MI. 29 In a recent prospective study of coronary artery atherosclerosis, the incidence of new coronary ischaemic events from non-significant coronary artery stenoses was 11.6% at 3.4 years, 19 a rate similar to the one observed in group B.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, thallium scanning may not be fully reliable as a predictor of asymptomatic significant coronary artery disease, especially in patients with left main or three vessel disease who are most at risk of post-operative and longterm MI. 29 In a recent prospective study of coronary artery atherosclerosis, the incidence of new coronary ischaemic events from non-significant coronary artery stenoses was 11.6% at 3.4 years, 19 a rate similar to the one observed in group B.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies also suggested that preoperative coronary revascularization improves the cardiac outcome early after major noncardiac surgery (18,19). We have recently shown that preoperative coronary revascularization in patients with moderate to severe reversible ischemia on thallium scanning is associated with improved long-term survival after major vascular surgery (9). However, none of the previous studies explored the association of PTS results or coronary revascularization with postoperative cardiac troponin and ischemia duration after major surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible ischemia on preoperative thallium scanning (PTS) predicts adverse postoperative and long-term cardiac events. It has also been recently shown that significant ischemia on PTS is an independent predictor of long-term mortality after major vascular surgery and that coronary revascularization in patients with significant ischemia on thallium scanning is associated with improved long-term survival (9). The effects of preoperative factors, in particular, PTS findings and coronary revascularization, on low-level versus conventional postoperative troponin elevation after major vascular surgery have not been previously investigated.…”
Section: See Page 576mentioning
confidence: 99%
“…The patients enrolled in the study were not low risk by virtue of the fact that 74% were at increased cardiac risk by either the Eagle criteria [22], the Revised Cardiac Risk Index [2], or a high-risk stress imaging test [33]. Two thirds of the patients had multivessel coronary artery disease and two thirds of those patients undergoing stress image tests had high-risk test results, consistent with multivessel coronary artery disease.…”
Section: Interpretation Of the Carp Trialmentioning
confidence: 99%
“…The incidence of a perioperative myocardial infarction among individuals undergoing a vascular operation approaches 20% and can be predicted by abnormalities on preoperative stress imaging with thallium [50]. Among those individuals with a perioperative myocardial infarction, the mortality is increased nearly fourfold during a 6-month postoperative follow-up period [51,52] and may predict long-term mortality [33], although this is not certain beyond the first postoperative year [53]. • The causative factors that relate to a new myocardial infarction in the postoperative phase are not necessarily related to a severe stenosis within a coronary artery that has not been revascularized.…”
Section: Postsurgical Surveillance and Risk Stratificationmentioning
confidence: 99%